UPAYA PEMBERDAYAAN SDM DESA MELALUI PELATIHAN TATA KELOLA ADMINISTRASI YANG BAIK DAN BENAR PADA KARANG TARUNA DI DESA CIBENING - Desi Puspita Sari; Fadhillah Fadhillah (Universitas Islam 45 Bekasi, 2022)
Community empowerment is important for improving skills and potential. Empowerment can be anything, one of which is related to administration. Administration is an important part especially in an organization. Good administrative governance will certainly support the progress of an organization. The purpose of this activity is to provide an understanding related to good and correct administrative governance to cadet coral members and provide training in making official letters that are in accordance with the rules so that cadet coral members are able to manage administration properly and correctly. What underlies the conduct of this administrative governance training is because there are still some members of Karang Taruna Desa Cibening who do not understand related to good and correct administrative governance. This training was conducted in Kampung Cigebang RT 002 RW 002 Ciening Village Setu District of Bekasi Regency. The methods used in this program are 1) Observation, 2) Community Education, 3) Training and 4 Evaluation. The results of the training showed that the cadet charcoal members became more understanding about good and correct administrative governance, those who previously did not understand how to make letters more understanding and were greatly helped by the existing letter making module.